2014
DOI: 10.3349/ymj.2014.55.4.1101
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Psychological and Music Interventions in Elderly Patients Undergoing Spinal Anesthesia: Effect on Anxiety, Heart Rate Variability, and Postoperative Pain

Abstract: PurposeThe aim of this study was to evaluate the effects of perioperative psychological and music interventions in elderly patients undergoing elective surgery on anxiety, post-operative pain, and changes in heart rate variability (HRV) to ascertain if perioperative psychological and music interventions can affect overall anxiety levels.Materials and MethodsFourty elderly patients undergoing elective surgery were randomized to two groups; one group received psychological and music intervention, and the other w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…Psychological counseling, music, preoperative education, hypnosis, gabapentin, and pregabalin have been shown to decrease anxiety and improve outcomes after various surgical procedures. [41][42][43][44][45][46] Although there is no literature to support or refute the use of selective serotonin reuptake inhibitors or serotonin norepinephrine reuptake inhibitors in the management of preoperative anxiety, these classes of drugs are routinely used to treat generalized anxiety disorder and could be beneficial in the perioperative period in select patients undergoing surgical procedures for TMD. Further outcome-based studies in the surgical management of TMD that assess anxiety are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological counseling, music, preoperative education, hypnosis, gabapentin, and pregabalin have been shown to decrease anxiety and improve outcomes after various surgical procedures. [41][42][43][44][45][46] Although there is no literature to support or refute the use of selective serotonin reuptake inhibitors or serotonin norepinephrine reuptake inhibitors in the management of preoperative anxiety, these classes of drugs are routinely used to treat generalized anxiety disorder and could be beneficial in the perioperative period in select patients undergoing surgical procedures for TMD. Further outcome-based studies in the surgical management of TMD that assess anxiety are needed.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that anxiety leads to activation of sympathetic system causing stimulation of hypothalamic autonomic system and rising of heart rate, which is slowed down by music due to reduction in anxiety. 9 Other recent study by Kahloul M et al, on patients under general anaesthesia (GA) also showed lowering of HR with music. 10 Shu MW et al, and Ebneshahidi A et al, in their studies did not find any change in HR between music and control groups which is contrary to our study results.…”
Section: Resultsmentioning
confidence: 93%
“…This difference in values were highly significant (p = 0.009) (Table 4). [1][2][3][4][5][6][7][8][9][10] Researchers have quoted various mechanisms, which include release of neurogenic endorphins by music helping to decrease the anxiety and stress.…”
Section: Resultsmentioning
confidence: 99%
“…This study concluded that intervention via use of music in perioperative period significantly reduced sympathetic and enhanced parasympathetic activity by reducing anxiety. 9 Another research evaluated effect of music on 100 patients undergoing caesarean sections. Authors found a highly significant lowering of anxiety and a high patient satisfaction score in music group as compared to control group.…”
Section: Music and Anxietymentioning
confidence: 99%